2016
DOI: 10.1016/j.molimm.2016.04.010
|View full text |Cite
|
Sign up to set email alerts
|

A triad of molecular regions contribute to the formation of two distinct MHC class II conformers

Abstract: MHC class II molecules present antigen-derived peptides to CD4 T cells to drive the adaptive immune response. Previous work has established that class II αβ dimers can adopt two distinct conformations, driven by the differential pairing of transmembrane domain GxxxG dimerization motifs. These class II conformers differ in their ability to be loaded with antigen-derived peptide and to effectively engage CD4 T cells. Motif 1 (M1) paired I-Ak class II molecules are efficiently loaded with peptides derived from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 21 publications
(88 reference statements)
2
18
1
Order By: Relevance
“…6a), an observation that has also been made in bicellar environments (Salnikov et al 2019). It is notable that both sequences encompass GxxxG motifs that have been identiied to promote dimerization within membrane environments (Dixon et al 2014;Drake and Drake 2016;King and Dixon 2010;Russ et al 2000;Travers et al 1984). Previous structural studies of dimers interacting through the GxxxG motif were characterized by relatively high crossing angles (Itkin et al 2017;Sato et al 2009;Smith et al 2002) in agreement with the tilted arrangement observed here (Figs.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…6a), an observation that has also been made in bicellar environments (Salnikov et al 2019). It is notable that both sequences encompass GxxxG motifs that have been identiied to promote dimerization within membrane environments (Dixon et al 2014;Drake and Drake 2016;King and Dixon 2010;Russ et al 2000;Travers et al 1984). Previous structural studies of dimers interacting through the GxxxG motif were characterized by relatively high crossing angles (Itkin et al 2017;Sato et al 2009;Smith et al 2002) in agreement with the tilted arrangement observed here (Figs.…”
Section: Discussionsupporting
confidence: 88%
“…These facts deine MHC class II molecules as proteins with important biomedical function. While molecular determinants in peptide binding of the extracellular domains of MHC II DQ proteins have in many cases been characterized in great detail (Painter and Stern 2012), the importance of the transmembrane in heterodimer assembly, the formation of distinct conformational subclasses and their relationship to biological function have been explored by biophysical approaches, site-directed mutagenesis and the analysis of epitope expression (Dixon and Roy 2019;Drake and Drake 2016). Nevertheless, many open questions remain about the roles of their transmembrane domains in assembly, traicking, peptide loading, presentation and speciically their interactions with lipids (Anderson and Roche 2015).…”
Section: U N C O R R E C T E D P R O O F Introductionmentioning
confidence: 99%
“…Whereas, for MHC II the immunogenic peptide binding to its extracellular domains has been investigated in great detail (Painter and Stern, 2012), less is known about the transmembrane domains and their interactions with lipids during assembly, trafficking, peptide loading and presentation (Anderson and Roche, 2015; Dixon and Roy, 2019). The assembly of transmembrane domains into heterodimers, the presence of distinct conformational subclasses and their correlation with biological function have been studied by biophysical approaches, site directed mutagenesis and the analysis of epitope expression (Drake and Drake, 2016) while little is known about the role of sphingomyelin in such process and how SM-C18 interacts with the transmembrane domains.…”
Section: Introductionmentioning
confidence: 99%
“…1Cb) as well as multimerized 11-5.2 mAb (which will selectively aggregate M1 I-A k class II, Fig. 1C), and the B cell calcium response was monitored as previously reported (24) [the two anti-I-A k mAbs bind distinct epitopes, and there is no cross-inhibition of binding (21,25)]. As illustrated in Fig.…”
Section: Immunohorizonsmentioning
confidence: 99%
“…In contrast, Ia.2 -I-A k molecules have the b-chain GxxxG motif paired with the a-chain C-terminal M2 motif (i.e., M2-paired MHCII [M2 MHCII]). Further study defined three molecular regions involved in the formation of the Ia.2 epitope that marks M1-paired I-A k MHCII [i.e., TM domain GxxxG motif pairing/cholesterol binding(19,20,22,23,25,26), a-chain Glu-71(25), and the a-chain Arg-52-b-chain Glu-86 interchain salt bridge(25)]. This foundational work has led to the development of the M1/M2 hypothesis [Fig.…”
mentioning
confidence: 99%